Упростите выражение: 1). 5(x+2y)-3(2x+y)=...
2). -2(x-y)-3(y+x)=...
3). (x-2)+2(x+1)=...
4). -x(2x-3)+3(2-x)=...​

STARBOY47 STARBOY47    1   13.12.2020 08:51    1

Ответы
hunateВадим2827854 hunateВадим2827854  12.01.2021 09:02

5(x+2y)-3(2x+y)

5x-10y-6x+3y

x(5-6)-y(-10+3)

-1x-7y

2)-2(x-y)-3(y+x)

-2x-2y-3y-3x

X(-2-3)-y(-2-3)

5x-5y

4)-x(2x-3)-3(2-x)

-2x²-3x-6-3x

-2x²-x(-3-3)-6

-2x²-6x-6

ПОКАЗАТЬ ОТВЕТЫ
asvpdsh asvpdsh  12.01.2021 09:02

Объяснение

1). 5(х+2у)-3(2х+у)=5х+10у-6х-3у= -х+7у;

2). -2(х-у)-3(у+х)= -2х+2у-3у-3х= -5х-у;

3). (х-2)+2(х+1)=х-2+2х+2=3х;

4). -х(2х-3)+3(2-х)= -2х²+3х+6-3х= -2х²+6.

Не забывайте подчёркивать подобные.

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра